The impact of fuel injection pressure on the exhaust emissions of a direct injection diesel engine fueled with biodiesel-diesel fuel blends - SAYIN, CENK; GÜMÜŞ, METİN (ELSEVIER SCI LTD, 2012)
In this study, the effects of fuel injection pressure on the exhaust emissions and brake specific fuel consumption (BSFC) of a direct injection (DI) diesel engine have been discussed. The engine was fueled with biodiesel-diesel blends when running the engine at four different fuel injection pressures (18, 20, 22, and 24 MPa) and four different engine loads in terms of mean effective pressure (12.5, 25, 37.5, and 50 kPa). The results confirmed that the BSFC, carbon dioxide (CO2), nitrogen oxides (NOx) and oxygen (O-2) emission increased, smoke opacity, unburned hydrocarbon (UHC) and carbon monoxide (CO) emissions decreased due to the fuel properties and combustion characteristics of biodiesel. On the other hand, the increased injection pressure caused to decrease in BSFC of high percentage biodiesel-diesel blends (such as B20, B50, and B100), smoke opacity, the emissions of CO, UHC and increased the emissions of CO2, O-2 and NOx. The increased or decreased injection pressure caused to increase in BSFC values compared to original (ORG) injection pressure for diesel fuel and low percentage biodiesel-diesel blends (B5). (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biodiesel; Injection pressure; Direct injection diesel engine; Exhaust emissions; OIL METHYL-ESTER; FRYING PALM OIL; COMBUSTION CHARACTERISTICS; SUNFLOWER OIL; PERFORMANCE; OXIDATION